The feasibility of storing ovarian tumor cells on databasing paper: establishing a library of ovarian cancer DNA. Issue 1 (1st January 2007) - Galaal, K.; Meirovitz, M.; Hussain, R.; Allcroft, L.; Sullivan, N.; Lopes, A.; Edmondson, R. J.
Abstract : The purpose of this study was to assess the feasibility of establishing a library of ovarian cancer nucleic acids using paper matrix by: 1) confirming the stability of DNA stored on paper matrix over a prolonged period of time, 2) determining the amount of genetic material required for storage, and 3) establishing the stability of RNA. Tumor tissue from 66 patients with ovarian cancer was collected intraoperatively, frozen, and dissociated with collagenase and trypsin. A cell suspension was then prepared and spotted onto the paper. The numbers of cells that were stored on the paper were counted using a hemocytometer. The cell suspension was serially diluted and spotted on the paper matrix until the minimum cell number that can be stored and produce a PCR product was determined. PCR, STR genotyping and direct sequencing were performed on tissue stored on the paper matrix. FTA® paper was used as RNA template, and RT PCR converted the RNA to cDNA. Ten to 50 mg of ovarian cancer tissue was stored on FTA® paper. We stored 7 × 10 4 cells on ISOcode® paper and 18 × 10 4 cells on FTA® and obtained extractable DNA. PCR analysis on cards with DNA stored 18 months ago enabled us to establish the stability of DNA after storage. RNA was stable for 6 months when stored on FTA® cards. Since genetic material is extractable from the paper matrices after passage of time, it could be a suitable medium for the storage of genetic material in cancer tissue banks.